Implementasi Modul Ajar STEM-PjBL Melalui Proyek Pembuatan PLTAM dari Barang Bekas: Studi Deskriptif Kualitatif pada Pembelajaran IPA - Silmiah, Nadia Nuri; Sopiah, Imas Pipih; Amirudin, Mahdiyina; Sukmawardani, Yulia; Saadah, Sumiyati (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to describe the implementation of a STEM-based teaching module  Project Based Learning (PjBL) through a project to build a Mini Hydroelectric Power Plant (PLTAM) from used materials and to analyze students' learning experiences in science learning. The study used a qualitative descriptive approach with a descriptive study design conducted at SMPN 1 Cilengkrang. The research procedure included the stages of problem orientation, project planning, prototyping, testing, and reflection. Data collection was carried out through observation, interviews, documentation, and analysis of student projects. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and techniques. The results showed that the implementation of the STEM-PjBL teaching module took place systematically through five project stages. Project activities encouraged active student involvement, collaborative work, and the integration of elements of science, technology, engineering, and mathematics. Students demonstrated a better understanding of the principles of converting water energy into electrical energy. The use of used materials increased students' creativity and environmental awareness. The questionnaire data showed a very positive response, with an average score above 4.2 and a percentage of agree/strongly agree reaching 83.3%-100%. The implementation of the STEM-PjBL teaching module through the hydropower project using recycled materials was able to create more contextual, meaningful, and student-centered science learning, and is worthy of being used as an innovative alternative in renewable energy learning in junior high schools.